PERANAN PEMERINTAH DALAM KAITANNYA DENGAN PERJANJIAN FRANCHICE BENTUK USAHA ALFAMIDI DI SAMARINDA - Yudhi Bintoro (Universitas 17 Agustus 1945 Samarinda, 2014)
AbstractIn Indonesia's economy, one of the fields is quite prominent is the trade sector. It has three main activities, namely the economic system of production, distribution and consumption. One way of distributing the expanding business internationally is through licensing, as an alternative attempt to get closer to consumers in a country as well as to reduce the impact of transport costs high export, as well as the risk of loss of product from the market as a result of transportation risks and embargo which may done politically.Freedom of contract would only result in maximum benefit when there is an unfair distribution of wealth it or is not satisfactory, then the exchange generated by the agreement will reflect the injustice and discontent. Important qualification of the progress of freedom of contract to produce a satisfactory distribution was almost completely been ignored by the classical economists are rarely questioned about inequality in society. The use of goods produced in Negeri.Sebagai suppliers or the Franchise thus get boost and develop small and medium enterprises in Samarinda.